Evaluating nitrogen release rates of commercial slow-release urea products using Brix value analysis: a validation study comparing two methods - Fernández Wallace, Trinidad; Zenobi, Marcos; Bollatti, Juan; Boetto, Catalina; Salloum, María Soraya (2024)
H INDEX: 11. Guía de la Biblioteca de la Universidad de Huelva: Evaluación de la Investigación: Índice H. https://guiasbuh.uhu.es/c.php?g=655120&p=4605523